Indonesian EFL Learners Responses to Using ChatGPT: An Analysis Based on The TAM Model - Karolina, Venny; Querioz, Carla; Xaixanith, Toby; Farhan, Firda Islamaya (Journal of Education Reseach and Evaluation, 2025)
AI-powered tools are increasingly used in English language learning. Still, few studies have validated the Technology Acceptance Model (TAM) in assessing Indonesian students' responses to ChatGPT and the influence of academic level. This study aimed to evaluate the validity and reliability of a TAM-based questionnaire and examine the role of academic level in these responses. This study utilized a quantitative survey design. The research subjects consisted of 448 university students in West Kalimantan through stratified random sampling. The data collection method was an online survey administered through Google Forms. Confirmatory Factor Analysis (CFA) confirmed the construct validity and reliability of the TAM components. Statistical analysis showed that academic level significantly influenced Perceived Ease of Use (PEU), Perceived Usefulness (PU), Attitude Toward Use (ATU), and Behavioral Intention (BI), although with a small effect size. Senior students reported higher perceived usefulness and intention to use ChatGPT, while first-year students showed lower engagement, indicating that academic progression influences AI adoption. These findings highlight the need for structured AI literacy programs, especially rapid writing skills training, to increase student engagement.